Linkage Between Mangrove Seedling Colonization, Sediment Traits, and Nitrogen Input - He, Ziying; Yen, Lingwei; Huang, Hongjie; Wang, Zihao; Zhao, Lili; Chen, Zhonghan; Lee, Shing Yip; Peng, Yisheng (Frontiers in Marine Science, 2022)
Mangroves around the world settle along coasts and estuaries, where they usually encounter aquaculture effluent that causes eutrophication and regulates the nitrogen cycle in their ecosystems. Moreover, the physical–chemical features of sediment in mangrove habitats might be altered by coastal wind, waves, and currents more frequently under the condition of increasing extreme climatic events. These events affect the process of colonization/regeneration of mangroves. To study how exogenous nitrogen input and sediment texture affect root system establishment of mangrove propagules and the early growth of seedlings, in turn, we set up a mesocosm experiment to explore the morphological and physiological responses of the root system of two mangroves, i.e., Kandelia obovata and Sonneratia apetala. We found that the root morphological features of mangrove seedlings mostly showed significant differences across the sediment texture treatment; K. obovata seedlings were more intensively influenced than S. apetala seedlings. It could be ascribed that the roots of K. obovata seedlings were more sensitive to sediment texture than S. apetala seedlings. Conversely, the treatment of exogenous nitrogen input showed a slighter even non-significant influence on the root features of mangrove seedlings. These results suggest that the seedlings of S. apetala and K. obovata performed similarly. In estuaries and coasts featuring eutrophication and various sediment textures, the conservation and restoration of mangroves should consider these conditions to ensure the sustainable development of mangroves.